Can assertiveness skills training (AST) and Dialectical behaviour therapy treat social skills deficit of peer rejected in-school -adolescents in Ibadan, Nigeria? (2019)
Students with deficit social skills tend to have problems of interactions with peers and teachers which indirectly affect their academic performance. Literature on management of social skill deficit among peer rejected adolescents in Oyo state is limited. This study therefore, utilized Assertiveness Skills Training (AST) and Dialectical Behaviour Therapy (DBT) to manage deficit social skills among students diagnosed as peer rejected in junior secondary schools in Ibadan, Oyo State. Pre-test-post-test control group, quasi experiment design with 3x2x3 factorial matrix was adopted. Ninety students (Males= 40; Females=50) with age range of 10 to 15 years were purposively drawn from three public secondary schools in Ibadan. Social Peer Rejection Scale (α =0.81) was used to draw peer rejected students, while Social Skills Rating Scale (α = 0.86) and Self-consciousness Scale (α=0.70) were utilized as outcome measures. The students were randomly assigned to treatment conditions. The Experimental groups were exposed to 10 sessions of therapies while the control group served as the comparison group. Results showed that there was a significant main effect of treatments [F (2, 75) = 8.761, p< 0.05, η2= 0.189] on social skills of the participants. Those treated with AST had superior mean gain ( x = 68.64) over DBT ( x = 66.09) and Control Group ( x =55.40). There was interaction effect of treatments and gender [F (2, 75) = 11.123, p<0.01, η2= 0.229]. The interaction effect of treatments and levels of self-awareness was also significant [F(4,75)= 3.081, p<0.05, η2= 0.141] on social skills. There was no three way interaction effect of treatments. This outcome provides empirical supports for the use of AST and DBT to remediate social skill deficit. The researchers recommended the use of the therapies for the enhancement of social skills in school settings.